Strategic understanding of Malaysian online customers’ service quality preference through demographic customer profiling and e-product bundling - Ong, Derek Lai Teik *; Ho, Jessica Sze Yin * (2012)
In order to stay competitive in the arena of e-commerce, conventional e-marketing research have provided solutions to online businesses and marketing practitioners by understanding online purchasing behavior and thereby proposing various determinants influencing online purchasing behavior. Little research has been done in order to assist marketing practitioners to identify the precise online customer segmentation, making market targeting and positioning and use of effective marketing campaigns complex. Hence, this study aims to identify the appropriate online customer segmentation (product bundles) based on three determinants of online purchasing behavior, i.e. e-service quality, demographic profiles and types of product purchased. 680 useful data was collected from existing online shoppers and data mining technique was employed to identify the product bundles and decision trees were used for customer profiling. Findings have identified Tickets, Clothing and Travel product bundles as the basis of segmentation. Result from this study will assist online marketing practitioners to be conscious of online customers needs and astutely create marketing campaigns aiming at their targeted online customers segments